Lower Tremadocian (Ordovician) lingulate brachiopods from the Central Andean Basin (NW Argentina) and their biogeographical links - Lavié, Fernando Julián (2023)
A Lower Tremadocian (Tr1) lingulate assemblage from the Guayoc Chico Group (Pupusa Formation) is described and illustrated for the first time. The fauna consists of poorly preserved obolids referred to Libecoviella? sp. and Torobolus cf. subplanus Benedetto & Munoz, 2015, the acrotretid Eurytreta harringtoni Mergl & Herrera, 2015 and the siphonotretid Celdobolus skrikus sp. nov. This is the first record of the genus Celdobolus in South America, previously recorded from slightly younger strata of Bohemia and Belgium. The Tremadocian lingulate fauna from the Central Andean basin displays closest biogeographical similarity with the Bohemian and Avalonian assemblages and supports a poleward (in Ordovician coordinates) dispersal trajectory along the clastic platforms bordering the Amazonian and NW Africa cratons. On the basis of recent coupled ocean-atmosphere circulation models for the Lower Ordovician it is inferred that larvae could have been transported by the boundary cold-water Antarctica Current.